Development Fintech Ecosystem: Evidence of European Countries for Ukraine - Fedyshyn, Maiia; Abramova, Alla; Morozova, L; Lavrov, Ruslan; Kovalova, O; Malin, O. (International Journal of Computer Science and Network Security, 2022)
The growth of digitalization processes around the world, covering almost all areas of human life, including the Fintech sector. In the field of financial technology, radical changes are taking place with increasing levels of automation, openness and consumer focus. In addition, in the context of the spread of coronavirus infection, quarantine and forced isolation, the role of digital technology is coming to the fore worldwide, including in Ukraine. The purpose of the article is to assess the development of Fintech ecosystem of European countries and outline the strategic parameters of domestic Fintech development. The study concluded that the investment raised for the Fintech industry increases annually and the quality and size of transactions gradually increases. Today, Fintech maintains its position as one of the most attractive markets for venture capitalists and the image of an industry with high potential, especially in the era of open banking. The most attractive markets for investors are mature markets, such as the United States, Germany and the United Kingdom, and the preferred niches for investment - the vertical of payments and lending. Trends in investment activity in terms of investing in financial technologies are studied. Moreover, investors prefer businesses that already have a significant scale or considerable potential to achieve it and become sustainable businesses.
Keywords: Fintech companies; financial services market; digitalization; financial ecosystem; Sandbox